(untitled) (Revista científica Olimpia, 2019)
The work gives answer to a problematic of the capacitances: the insufficient development of the coordinative capacitances. Your objective is to apply drills that permit the development of the coordinative capacitances: equilibrium and space orientation in the 7-years female child of rhythmic gymnastics of the Bayamo municipality. The practical contribution of the investigation takes root in the application of drills directed to develop the capacitances of helping to plan the sport training in the athletes. It is drills they facilitate resolve the problematic material technician it exists in the area. The drills were adapted by keeping in mind the characteristics of the female child of gymnastics, as well as the potentialities that drink a toast the technical drills to perfect the class of training in the preparation of the gymnasts